The prevalence of lower urinary tract symptoms in Caesarean section patients’ first and seventh day of postpartum : Perbandingan Prevalensi Gejala Saluran Kemih Bawah pada Ibu Postpartum Hari pertama dan Hari Ketujuh secara Sectio Caesarea - Austin Julian; Johannes C. Prihadi; Yuma S. S. Indrajaya (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To compare the prevalence of Lower Urinary Tract Symptoms (LUTS) on the first day and the seventh day postpartum in Caesarian section patient Method: This cross-sectional study utilized the ICIQ-FLUTS LF (ICIQ-Female Lower Urinary Tract Symptoms-Long Form) and a questionnaire to screen for risk factors among postpartum patients who underwent C-section delivery at Santo Antonius Hospital, Pontianak, West Kalimantan. Data were collected twice, 12 hours after urinary catheter removal and on the seventh day of the postpartum period. The study sample consisted of 95 respondents. Results: Among the 111 total respondents, the majority were under 35 years old, multiparous, classified as obese, had no family history of Lower Urinary Tract Symptoms (LUTS), and had not used diuretics or traditional medicine. Significant differences were observed in the prevalence of LUTS between the first and seventh days of the postpartum period. Most symptoms showed a decrease on the seventh day, except for six symptoms: insensible urinary incontinence, hesitancy, urinary retention, feeling of incomplete emptying, bladder pain, and dysuria, which increased. Conclusion: In conclusion, our study suggests that the duration of the postpartum period affects the prevalence of LUTS following C-section delivery. However, it's important to acknowledge the limitations of this study, which may impact the understanding of LUTS progression during the postpartum period. Conclusion: In conclusion, we concluded that the duration of the postpartum period affects the LUTS after delivery with the method of C-section, but this study has many limitations which may affect the progressivity of LUTS in the Postpartum period. Keywords: Caesarean Section, ICIQ FLUTS Long From, Lower Urinary Tract Symptoms, Postpartum period Abstrak Tujuan: Untuk membandingkan prevalensi Gejala Saluran Kemih Bawah di hari pertama dan hari ketujuh postpartum pada pasien Sectio Caesarea. Metode: Desain penelitian berupa studi potong li.ntang dengan pengumpulan data menggunakan kuesioner terstruktur ICIQ FLUTS-LF dan kuesioner skrining dasar penelitian yang dilakukan 2 kali yaitu 12 jam setelah pelepasan kateter dan postpartum hari ke 7. Subjek penelitian ini adalah semua ibu postpartum dengan metode SC yang memenuhi kriteria inklusi dan eksklusi penelitian di RS Santo Antonius Pontianak, Kalimantan Barat. Jumlah sampel pada penelitian ini adalah 95 responden Hasil: Pada penelitian ini didapatkan subjek sebesar 111 responden yang mayoritasnya berusia kurang dari sama dengan 35 tahun, multipara, status gizinya obesitas, tidak memiliki riwayat keluarga yang mengalami LUTS, tidak mengkonsumsi obat-obatan tradisional dan obat-obatan diuretik. Terdapat perbedaan signifikan di prevalensi LUTS hari 1 dan 7 postpartum SC dengan mayoritas dari 16 gejala LUTS yang didata mengalami penurunan di hari ketujuh dibanding hari pertama, terkecuali 6 gejala LUTS yang mengalami peningkatan di hari ketujuh yaitu Insensible Urinary Incontinence, Hesitansi, retensio urin, perasaan tidak lampias setelah berkemih, nyeri kandung kemih, serta disuria. Kesimpulan: Dalam penelitian ini, peneliti menyimpulkan bahwa durasi masa postpartum berpengaruh pada keluhan LUTS yang dialami pasca persalinan secara Sectio Caesarea, akan tetapi, penelitian ini memiliki keterbatasan yang dimana terdapat banyak oleh faktor-faktor risiko tertentu yang dapat berpengaruh terhadap progresivitas LUTS Kata kunci: Sectio Caesarea, ICIQ FLUTS Long Form, Gejala Saluran Kemih Bawah, Masa Pasca Persalinan, Masa nifas, Postpartum